The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.18378/rvads.v13i1.5333
|View full text |Cite
|
Sign up to set email alerts
|

Índice de qualidade do solo em cultivo agroecológico e convencional no semiárido potiguar, Brasil

Abstract: Resumo:O uso e manejo inadequado em sistemas de cultivo na região semiárida podem declinar a capacidade do solo em sustentar a produção. O objetivo do estudo foi determinar o índice de qualidade do solo (IQS) em unidades experimentais agrícolas (UEA) irrigadas agroecológica e convencional, localizadas na comunidade de Sombras Grandes, Caraúbas, Rio Grande do Norte. As amostras simples de solo (0-20cm) foram coletadas no período de 2009 a 2012. Para determinar o IQS, utilizaram-se 11 indicadores de qualidade as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…For soil function 2, sum of bases (1.00%) and soil organic matter (3.34%) had the smallest participation. Santiago, Montenegro and Pinheiro (2018) evaluated the SQI in several experimental agricultural units and observed that, for the soil function responsible for nutrient supply and cycling, soil organic matter was one of the most remarkable indicators.…”
Section: Resultsmentioning
confidence: 99%
“…For soil function 2, sum of bases (1.00%) and soil organic matter (3.34%) had the smallest participation. Santiago, Montenegro and Pinheiro (2018) evaluated the SQI in several experimental agricultural units and observed that, for the soil function responsible for nutrient supply and cycling, soil organic matter was one of the most remarkable indicators.…”
Section: Resultsmentioning
confidence: 99%
“…Sistemas baseados na Agroecologia também constituem ferramentas transformadoras na superação das limitações do semiárido, conforme Ferreita et al (2011) já apontou em seus estudos sobre a sustentabilidade de agrossistemas com barragens subterrâneas na Paraíba. Santiago et al (2018) realizou uma comparação entre a qualidade do solo em cultivos irrigados agroecológicos e convencionais, atestando positivamente os impactos da utilização de práticas da agroecologia em face ao manejo tradicional.…”
Section: Tecnologias Sustentáveis Para a Gestão De Recursos Hídricosunclassified
“…DCW rates at deeper layers were similar to those at the surface, indicating a translocation of material, especially at dose 240 m³ ha -1 , in which there was an 81% DCW reduction between layers 0-0.20 m and 0.20-0.40 m. In fact, biosolid triggered decrease of DCW through an increase of applied doses that, in turn, may directly affect the soil's compact capacity. According to Santiago et al (2018), increase in MOS provided a better soil structure, a decrease in DCW, and an increase of flocculation degree.…”
Section: Dispersed Clay In Water (Dcw)mentioning
confidence: 99%